Modeling Collisional Excitation of [O i] Fine Structure Line Emission from PDRs. I. Homogeneous Clouds - Goldsmith, Paul F. (The Astrophysical journal, 2019)
Atomic oxygen (O0) plays a critical role in determining the structure of photon-dominated regions (PDRs), but reliable modeling of its emission has been hampered by the high optical depth of the 63 m fine structure line and complexities in the excitation of the relevant fine structure levels. We discuss here radiation produced by collisional excitation of the submillimeter fine structure lines of atomic oxygen ([O I]) using recent calculations of rates for collisions with atomic and molecular hydrogen. We employ the Molpop-CEP code to include the effects of optical thickness in slab models that are characterized by uniform oxygen abundance, hydrogen density, and kinetic temperature. The particular spontaneous decay rates and collisional excitation rates connecting the three O0 fine structure levels result in population inversion of the upper, 145 m transition. The effects of trapping are rigorously included and are reflected in the resulting line profiles that exhibit prominent self-absorption even with uniform physical conditions. We present figures for analyzing the two fine structure lines based on the intensity of the 63 m line and the 145 m/63 m line ratio. For the clouds considered, the results for line intensities and line ratios are modestly different from those obtained with a large-velocity-gradient model, but the ability to calculate line profiles is an additional powerful tool. Comparison of the model results with observed line profiles suggests that cloud models with varying physical conditions are required to optimally utilize [O I] fine structure line emission to trace the energetics of PDR regions and the feedback from massive, young stars.